Формування цільових груп з надійності електропостачання для впровадження стимулюючого регулювання тарифів на елетроенергію - Сайчук, Ю. С.; Замулко, А. І. (Енергетика і автоматика, 2017)
UDC 621.311FORMING A TASK FORCE WITH A RELIABLE POWER SUPPLY FOR THE INTRODUCTION OF INCENTIVE REGULATION OF TARIFFS ELECTRICITYY. Saychuk , A. Zamulko Now the question of reliability of electricity Ukraine is considerably inferior industrialized countries, due to the technical condition of their distribution networks. Thus, according to estimates, the average depreciation for Electricity energy facilities of some organizations is 60% or more. Along with the physical wear of electric power was their obsolescence. The technical level of most substations is identical to 30 - year old in developed countries. Inadequate infrastructure impedes the development of the market and limit the possibility of uninterrupted and quality power supply.In most industrialized countries has long been regulated range not only reliability, but also their thresholds. This contributed to the organization for Electricity these countries have equipped their respective distribution networks and switching equipment created a system of monitoring and control reliability (Outage management system (OMS).Introduction of OMS problem can be solved by implementing partitioning network switching devices and their automation. Of course, such steps require significant investment, the use of technical and economic analysis and justification. Therefore, the use of optimization problems, allowing the most efficient decisions in terms of financial resources and limiting the regime and take into account technological limitations.Solving this problem can be achieved by introducing a tariff differentiation criterion for the reliability of electricity supply.The purpose of research - the formation of task forces for Electricity organizations with the peculiarities of their structure, technical characteristics and performance reliability of power using a system of differential tariffs.Materials and methods of research. Regions Ukraine significantly differentiated by the factor conditions, the level of economic development, levels of industry, the level and structure of consumption of electricity and so on. The main reason for the uneven distribution by region due to significant differences in the levels of socio-economic development and deepening of interregional disparities and the concentration of economic activity and financial results in the more developed regions.This differentiation in regions heavily influences the structure of organizations for Electricity, where nature and power consumption requirements for reliability of electricity depending on economic development, industrial structure and economic conditions generally differ.Using multivariate cluster analysis, conducted for Electricity clustering organizations of Ukraine. For the clustering software package was used STATISTIKA.Results. In the process of clustering was decided to group 5 of the target groups. The first cluster includes the largest organization for Electricity of branched structure, and the predominance of urban over rural and highest number of legal entities (companies) who might be interested in reliable electricity supply. Integrated better reliability than other clusters, due to better reliability of power supply per capita and sophistication cable networks.The fourth cluster is characterized for Electricity affiliate organizations with a predominance of rural over urban. Integrated reliability among the worst, because of the large number of routes.Clusters 2 and 3 are almost identical in structure for Electricity organizations that are inherent to them. However, they differ on the reliability of power supply. Supplier to, members of the 3 groups are more lasting interruptions in electricity supply, but their lower frequency than in group 2. These data indicate the different technical condition of the cable and air networks, electricity supply companies in each group.In Cluster 5 is only one supplier to. This can be explained by its feature, it focuses on only one power supply in Kyiv which explains its particular structure and process power.ConclusionsDue to increasing demands on the reliability of power supply, entry of Ukraine into the European Energy Community is necessary to move to incentive regulation in the electricity and the introduction of new criteria of differentiation electricity tariffs for the reliability level of power consumption.Given the characteristics of the supply of electricity, the first stage should be the research for Electricity organizations on the features of their structure, technical characteristics and performance reliability of power supply and formed on selected indicators relevant target groups (clusters) that will systematically and balanced approach to the introduction of incentive regulation.